1991
DOI: 10.1088/0022-3727/24/9/020
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous thermally induced fading of annealed and unannealed LiF:Mg, Ti (TLD-100, Harshaw) using computerized glow curve deconvolution

Abstract: Computerized glow curve convolution (CGCD) has been used to study the thermally induced room-temperature fading of both annealed and unannealed LiF:Mg, Ti following gamma ray, thermal neutron and alpha particle irradiation. The authors confirm the anomalous growth of peak 4 due to trap conversion in both types of material. However, they find no evidence for the growth of peak 5 in either material for any of the types of radiation studied. Their results similarly to not confirm the details of the differences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…As mentioned previously, published studies [19][20][21][22] showed that the determination of E a and s mainly depends on the prior knowledge of b and the exact number of glow peaks in the glow curve. Therefore, to find the order of kinetics of each individual glow peak, the variable dose method was first used.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned previously, published studies [19][20][21][22] showed that the determination of E a and s mainly depends on the prior knowledge of b and the exact number of glow peaks in the glow curve. Therefore, to find the order of kinetics of each individual glow peak, the variable dose method was first used.…”
Section: Resultsmentioning
confidence: 99%